Implementation of the Halal Product Guarantee Law in Indonesia by the Department of Industry and Trade Cooperatives of Bima City - Hakim, Lukmanul; Putri, Aisyah Karnila Nady (Universitas Islam Negeri Raden Fatah Palembang, 2022)
The obligation to register a halal certificate is stated in Article 4 of The Halal Product Guarantee Laws